Μιχαήλ Ψελλός: η ματιά του φιλότεχνου - ΑΓΓΕΛΙΔΗ, Χρ. (Byzantina Symmeikta, 1998)
Christine G. Angelidi Michael Psellos: The Eye of the Connoisseur The descriptions of works of art of the middle Byzantine period are more or less accurate in regard to the reconstruction of the objects as perceived by their authors. However, whatever literary genre they belong to, the ekphraseis usually concentrate on specific parts of religious works of art and their theological explanation. Thus, the artistic product is never perceived as a whole nor do the authors investigate the connexion between the accomplished creation and its conceptual background. As for the descriptions of antique sculptures dating from the same period, the authors seem to have used those particular themes only in an attempt to stress their own literary skills. An interesting exception is, once again, provided by the ekphraseis of Michael Psellos and namely his ‘Description of a sculpture representing the resting Cupid'. In this brief article we argue that Psellos' text marks out an important shift from the traditional perception and commentary of the work of art and specifically of an antique one. Not only does he describe in detail this marble sculpture (probably a marble copy of a hellenistic or imperial bronze sculpture), but also deals with the choice of the material as well as the choice of this particular type of Cupid. Furthermore, he stresses the perfection of the artist's achievement, which enables the connection between the form of the sculpture and its theoretical content. For his commentary, Psellos draws material from Plato's dialogues, combining platonic concepts in order to define his own theory of Beauty and Love. Two more points of Psellos' ekphrasis are discussed: the value of the sight as the first of the senses leading to philosophy, and the importance of the infant's body as a symbol of purity. Those two characteristics connect our text to the brief praise Psellos dedicated to his grandson ca. 1070.